Hulu ke Hilir: Jaringan dan Sistem Perniagaan Sungai Kerajaan Srivijaya - Sadzali, Asyhadi Mufsi (Paradigma: Jurnal Kajian Budaya, 2019)
The Kedukan Bukit inscription was written in 682 AD. It is considered as the oldest inscription related to the kingdom of Srivijaya and an authentic proof of the advanced maritime culture of Srivijaya. This argument is supported by the fact that, geographically, Sumatra is endowed with hundreds of large and small rivers that have generated abundant natural resources from its upstream to downstream areas. Srivijaya must have utilized these natural conditions to facilitate the distribution of its trade commodities— pepper, camphor, resin, and gold—from the upstream regions (flowing through countless tributaries to the main rivers) to the coastal areas, and even further to the various ports in Southeast Asia. Archaeological methods were used to identify and analyze a number of findings in the form of ancient boat artifacts from Srvijaya period in terms of both their respective forms and positions as they were unearthed along the Batanghari and Musi watersheds, from the upstream to estuary areas. From these findings, it can be inferred that Srivijaya managed to build a pattern of distribution network of trade commodities and to develop a sophisticated boat technology to support it. The commodity distribution network started from the upstream areas, namely the feeder points, all the way down to the downstream areas, namely the collecting centers; then, the commodities would be transported to the estuary, namely the main port of Srivijaya, and then carried to various other ports throughout Southeast Asia. The development of boat technology is the second key to the success and effectiveness of the pattern of trade commodity distribution that Srivijaya created from its upstream to downstream areas. The combination of such distribution network pattern and the development of boat technology has successfully established Srivijaya’s image as the most influential maritime power in Southeast Asia in the ancient period.